MULTICUTURAL CLASSROOM: TEACHER’S REFLECTION IN TEACHING ENGLISH FOR INTERNATIONAL STUDENTS FROM NON-ENGLISH SPEAKING COUNTRY - Rohfin Andria Gestanti; Elok Putri Nimasari; Restu Mufanti (EXPOSURE : JURNAL PENDIDIKAN BAHASA INGGRIS, 2018)
This present article aimed to elaborate the challenging problems that have been encountered by multicultural classroom teacherand how to deal with it. Heterogeneity in classroom is a common issue in language learning, especially with the involvement of multiculturalism. In this globalization era, the emergence of educational exchange causes students from a country takes their higher education in another country having better quality and reputation. Those students are commonly addressed as international students. The enrollment of such students is perceived advantageous for the university since it improves the international recognition. However, it also requires some efforts concerning the multicultural issue such as language, so that the students may successfully accomplish their study in a country which the native language is different from their native. With regard to this condition, the use of international language as a means of communication is unavoidable. However, in some circumstances, the use of native language in which the students take their study is more required, depending on the educational policy in appointed university. There are several students from Thailand taking their study in a private university in Ponorogo. Concerning the language, most of them are not mastering both English and Indonesia. As a result, teaching those students might be challenging due to misunderstanding communication that may occur in the classroom, especially for students who do not enroll in English Department. It presents the author’s experiences in teaching English for specific purposes in Communication Science Department of this university.